Implementasi Internet of Things pada Smart Homestay sebagai Solusi Otomatisasi dan Keamanan Akomodasi di Sektor Pariwisata - Hermanto, Hermanto; Kamdan, Kamdan; Sanulqi, Ihsan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The advancement of Internet of Things (IoT) technology has driven the development of automation systems that enhance comfort and efficiency across various sectors, including hospitality management. This study aims to design and implement a smart homestay system capable of automatically and manually controlling electrical devices using ESP32 and Arduino Uno microcontrollers. The system is equipped with several sensors, such as BH1750 for light intensity detection, MQ2 for smoke and alcohol detection, as well as physical buttons and smart switches for room services including laundry, cleaning, and Do Not Disturb (DND). An Android application, developed using MIT App Inventor, serves as the user interface and communicates with the ESP32 via a local Wi-Fi network using a Web Server method. Experimental results show that the system effectively responds to both sensor input and user commands, displaying real-time data in the app. The automatic light control feature based on lighting levels, gas detection notifications, and room service buttons functioned as designed. The system also supports two-way control between physical buttons and the mobile application. Quantitatively, response times for LED control averaged less than 1 second, sensor readings were updated every 3 seconds, and service command success rates reached 100% in all test scenarios. Therefore, the smart homestay system offers a simple yet effective solution to improve service and comfort in small-scale accommodations.